God in early Christian thought: essays in memory of Lloyd G. Patterson - McGowan, Andrew Brian; Patterson, Lloyd George (Vigiliae Christianae, 2009)
Who is the Demiurge? : Irenaeus' picture of God in Adversus haereses 2 / Richard A. Norris -- God beyond knowing : Clement of Alexandria and discourse / Annewies van den Hoek -- God in early Latin theology : Tertullian and the Trinity / Andrew B. McGowan -- Knowing God in the Theological orations of Gregory of Nazianzus : the heritage of Origen / Joseph W. Trigg -- God and Methodius : use of, and background to, the term aprosdeēs as a description of God in the works or Methodius of Olympus / Katherina Bracht -- Patristic exegesis and the arithmetic of the divine from the Apologists to Athanasius / James D. Ernest -- The Holy Spirit in Gregory Nazianzen : the pneumatology of Oration 31 / Christopher A. Beeley -- Divine semiotics and the way to the triune God in Augustine's De Trinitatis / Khaled Anatolios -- Ephrem's doctrine of God / Ute Possekel -- Trinitarian theology in early Christian anaphoras / Robert J. Daly -- Theophany and the invisible God in early Christian theology and art / Robin M. Jensen -- God and the poor in early Christian thought / Susan R. Holman -- The persons in God and the person of Christ in patristic theology : an argument for parallel development / Brian E. Daley -- God and storms in early Christian thought / Robert M. Grant